Taxonomic, functional, and phylogenetic diversity of primate communities in Ecuador - Orellana-Vásquez, Hernán; Gavilánez-E., María Mercedes (THERYA, 2023)
One of the fundamental objectives of ecology is to study the relative importance of ecological, evolutionary, and stochastic processes in determining local community structure. Many studies have focused on taxonomic diversity, paying relatively little attention to other dimensions of biological diversity, such as phylogenetic and functional diversity. Little is known about how these dimensions relate to each other, and the ecological processes that influence their variation. In this study, we characterize these three dimensions of biodiversity in 14 primate communities from different ecosystems in Ecuador to understand possible mechanisms responsible for their assembly. Results show that coastal communities are taxonomically less diverse than those from the Amazon and present different functional groups. On the other hand, phylogenetic diversity is higher in Amazonian communities, showing a tendency for overdispersion (high values of MPDPD = mean phylogenetic distance per pair and low PSC = degree to which coexisting species are related). This indicates a possible influence of biological factors, such as competition, on community assembly. For all three dimensions, climatic variables were the most significant predictors of community structure, while vertical forest structure contributed significantly to variation in the phylogenetic dimension. The high functional diversity reported in this study highlights the importance and vulnerability of this group and the ecosystems they inhabit. Macroecological studies, such as the one presented here, allow a better understanding of community structure and provide important information for the development of conservation strategies.